2008
DOI: 10.1128/jb.01387-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling and Functional Analysis ofAgrobacterium tumefaciensReveals a General Conserved Response to Acidic Conditions (pH 5.5) and a Complex Acid-Mediated Signaling Involved inAgrobacterium-Plant Interactions

Abstract: Agrobacterium tumefaciens transferred DNA (T-DNA) transfer requires that the virulence genes (vir regulon) on the tumor-inducing (Ti) plasmid be induced by plant phenolic signals in an acidic environment. Using transcriptome analysis, we found that these acidic conditions elicit two distinct responses: (i) a general and conserved response through which Agrobacterium modulates gene expression patterns to adapt to environmental acidification and (ii) a highly specialized acid-mediated signaling response involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
141
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(162 citation statements)
references
References 76 publications
(136 reference statements)
9
141
0
1
Order By: Relevance
“…Regarding plant-associated bacteria, IAA has been shown to determine changes in bacterial gene expression in the nongall-forming phytopathogen D. dadantii (formerly Erwinia herbicola) 3937 [57], in Agrobacterium tumefaciens [58,59] and in the plant growth-stimulating rhizobacterium A. brasilense [60], in which its ipdC gene has been the only bacterial gene reported to possess an AuxRE in its promoter, as observed in the auxin-responsive genes of plants [48]. Similarly, in the yeast Saccharomyces cerevisiae, several IAA-inducible genes are regulated at high IAA concentrations by the fungal transcriptional activator YAP-1, which is able to bind to their promoters to induce a switch towards invasive behavior, together with an arrest of cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding plant-associated bacteria, IAA has been shown to determine changes in bacterial gene expression in the nongall-forming phytopathogen D. dadantii (formerly Erwinia herbicola) 3937 [57], in Agrobacterium tumefaciens [58,59] and in the plant growth-stimulating rhizobacterium A. brasilense [60], in which its ipdC gene has been the only bacterial gene reported to possess an AuxRE in its promoter, as observed in the auxin-responsive genes of plants [48]. Similarly, in the yeast Saccharomyces cerevisiae, several IAA-inducible genes are regulated at high IAA concentrations by the fungal transcriptional activator YAP-1, which is able to bind to their promoters to induce a switch towards invasive behavior, together with an arrest of cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In addition, several studies have shown that IAA is a signaling molecule in microorganisms because it affects gene expression in several microorganisms. 12,13 IAA can have a major impact on interactions between IAA-producing organisms. The auxin acts as an effector molecule between IAA-producing bacteria and plants, and bacteria -bacteria interactions have been discussed in several reviews.…”
Section: Introductionmentioning
confidence: 99%
“…The production of larger quantities of IAA at lower pH may be attributed to the natural ability of microbes to efficiently express the IAA synthesis in rhizospheric conditions (Yuan, Liu, Saenkham, Kerr, & Nester, 2008). The lightdark regime of 8-16 hours gave the highest synthesis of IAA.…”
Section: Discussionmentioning
confidence: 99%